Barriers to Hepatitis C Virus Treatment in a Canadian HIV-Hepatitis C Virus Coinfection Tertiary Care Clinic. (2008) - McLaren, Meaghan; Garber, Gary; Cooper, Curtis
Abstract : BACKGROUND: Despite demonstrated efficacy in HIV-hepatitis C virus (HCV) coinfection, not all patients initiate, complete or achieve success with HCV antiviral therapy. PATIENTS AND METHODS: All HIV-HCV coinfected patient consults received at The Ottawa Hospital Viral Hepatitis Clinic (Ottawa, Ontario) between June 2000 and September 2006 were identified using a clinical database. A descriptive analysis of primary and contributing factors accounting for why patients did not initiate HCV therapy, as well as the therapeutic outcomes of treated patients, was conducted. RESULTS: One hundred two consults were received. Sixty-seven per cent of patients did not initiate HCV therapy. The key primary reasons included: HIV therapy was more urgently needed (22%), loss to follow-up (12%), patients were deemed unlikely to progress to advanced liver disease (18%) and patient refusal (12%). Many patients had secondary factors contributing to the decision not to treat, including substance abuse (23%) and psychiatric illness (14%). Overall, 59% of untreated patients (40 of 68) were eventually lost to follow-up. Thirty-three per cent of referred patients started HCV therapy. Twenty-seven of 42 courses (64%) were interrupted prematurely for reasons such as virological nonresponse (48%), psychiatric complications (10%) and physical side effects (7%). Of all treatment recipients, 12 of 42 full courses of therapy were completed and three remained on HCV medication. Overall, eight of the 102 coinfected patients studied (8%) achieved a sustained virological response. DISCUSSION: Not all HIV-HCV coinfected patients who are deemed to be in need of HCV treatment are initiating therapy. Only a minority of patients who do receive treatment achieve success. Implementation of HIV treatment, patient retention, attention to substance abuse and mental health care should be the focus of efforts designed to increase HCV treatment uptake and success. This can be best achieved within a multidisciplinary model of health care delivery.